2023 ACM Conference on Fairness, Accountability, and Transparency 2023
DOI: 10.1145/3593013.3593998
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Target Multiplicity: Flexibility and Fairness in Target Specification under Resource Constraints

Abstract: Prediction models have been widely adopted as the basis for decisionmaking in domains as diverse as employment, education, lending, and health. Yet, few real world problems readily present themselves as precisely formulated prediction tasks. In particular, there are often many reasonable target variable options. Prior work has argued that this is an important and sometimes underappreciated choice, and has also shown that target choice can have a significant impact on the fairness of the resulting model. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…Missing from these assessments is an examination of arbitrariness in college admissions. Prior work on model multiplicity has shown that predictive tasks can be satisfied by multiple models that are equally accurate (e.g., at identifying students with academic merit) but differ in terms of their individual predictions (e.g., whether a specific applicant is considered a top applicant) [16,69]. This means that any number of seemingly minor decisions made by a college admissions office -down to something as simple as how to sample training data -could impact an individual applicant's outcome even if it does not majorly affect the ability of the college to identify students with academic merit.…”
Section: Measuring the Impact Of Admission Processes And Policies On ...mentioning
confidence: 99%
“…Missing from these assessments is an examination of arbitrariness in college admissions. Prior work on model multiplicity has shown that predictive tasks can be satisfied by multiple models that are equally accurate (e.g., at identifying students with academic merit) but differ in terms of their individual predictions (e.g., whether a specific applicant is considered a top applicant) [16,69]. This means that any number of seemingly minor decisions made by a college admissions office -down to something as simple as how to sample training data -could impact an individual applicant's outcome even if it does not majorly affect the ability of the college to identify students with academic merit.…”
Section: Measuring the Impact Of Admission Processes And Policies On ...mentioning
confidence: 99%